The Impact of Implementation Capacity on the Link between Infrastructure Financing and Success in Kenya's Vision 2030 Public Projects - Nguri, John W.; Ochieng, Dr. Duncan Elly; Wainaina, Prof. Gituro (International Journal of Project Management, 2024)
Purpose: This study examines the success factors influencing cost and time variances in public capital projects in Kenya, with a focus on identifying sectoral disparities and the role of financing and implementation capacity. It aims to provide insights into mitigating risks to achieve Kenya's Vision 2030 infrastructure goals. Materials and Methods: The study employs descriptive statistics and regression analysis to evaluate data on cost and time overruns across various infrastructure sectors, including roads, energy, and water and sanitation. The analysis explores the impact of infrastructure financing (internal, external, and PPP) and implementation capacity factors such as procurement, supervision, planning, and payment processes. Findings: The results reveal significant variability in cost and time overruns across sectors. The road sector recorded the highest mean cost overrun, while the energy sector exhibited the highest risk of cost overruns. Time overruns were also prominent, with the road sector experiencing the greatest variability. Internal financing increased both cost and time overruns, whereas external financing reduced them due to stringent oversight mechanisms. PPP projects, however, experienced notable overruns due to the complexities of multi-stakeholder management. Enhanced implementation capacity significantly mitigated both cost and time overruns, while delayed payments to contractors exacerbated project inefficiencies. Implications to Theory, Practice and Policy: The study emphasizes the need for enhanced risk management strategies tailored to sector-specific challenges. Strengthening implementation capacity through better procurement, planning, and supervision is critical to reducing variances. Policymakers should prioritize timely payments to contractors and adopt stricter accountability measures for internally and PPP-funded projects. Leveraging external financing's oversight benefits while simplifying PPP frameworks can further enhance the success of public capital projects.